2019
DOI: 10.1177/0363546519886260
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With a Noncontact Anterior Cruciate Ligament Injury to the Contralateral Knee After Unilateral Anterior Cruciate Ligament Injury in High School and College Female Athletes: A Prospective Study

Abstract: Background: The incidence of contralateral anterior cruciate ligament (CACL) injuries after recovery from a first-time anterior cruciate ligament (ACL) disruption is high in women; however, little is known about the risk factors associated with this trauma. Hypothesis: Patient characteristics, strength, anatomic alignment, and neuromuscular characteristics of the contralateral uninjured leg at the time of the first ACL trauma are associated with risk of subsequent CACL injury, and these risk factors are distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Of the 44 included studies, nine [ 53 , 57 , 59 , 61 , 67 , 68 , 70 , 85 ] were excluded from the meta-analysis due to being the only study reporting on a specific factor or using specific statistics that were not possible to calculate to odds ratios. The caracteristics and results of these studies are reported in online resource 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 44 included studies, nine [ 53 , 57 , 59 , 61 , 67 , 68 , 70 , 85 ] were excluded from the meta-analysis due to being the only study reporting on a specific factor or using specific statistics that were not possible to calculate to odds ratios. The caracteristics and results of these studies are reported in online resource 2.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have previously pointed to a possible role of hip and knee movement patterns and moments during functional tasks, as well as hop performance, for the risk of sustaining second ACL injuries (graft rupture and C-ACL injury combined) [ 30 , 39 , 113 ]. There is nevertheless limited evidence for lower extremity strength as a contributing factor to C-ACL injury risk [ 53 , 66 ] (Online resource 2). Given that demographic factors such as sex, age and family history cannot be changed, studies on risk factors that are modifiable are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight studies reporting joint laxity measures, five studies found an association with ACL (re)injury in at least one of the metrics assessed [ 14 , 15 , 33 , 46 , 60 ], while two found none [ 18 , 52 ]. One study was excluded from the analysis because of a potential risk of bias [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded from the analysis because of a potential risk of bias [ 27 ]. An association between the following metrics and ACL (re)injury was found for: (1) anterior knee stiffness (a 1 SD decrease in anterior stiffness of the knee was associated with a 2.37-fold increase in the risk of CACL injury) [ 33 ]; (2) generalized joint laxity (little finger extension and thumb opposition test were positive in the ACL injured) [ 14 ]; (3) side-to-side differences in knee laxity (for every 1.3-mm increase, the odds of ACL injury increased four-fold (95% CI, 1.68–9.69), and side-to-side difference in anterior knee laxity of 3 mm or greater had an OR of 2.4 of sustaining a contralateral ACL injury) [ 46 , 60 ]; and (4) decreased general joint laxity (GJL) (based on the Beigtohn GJL scale, where a larger number indicated a higher GJL; cases: 1.8 (1.3); controls: 2.7 (2.2)) [ 15 ]. No association was found for generalized laxity measures [ 18 , 46 ] or knee laxity in the sagittal plane [ 14 , 15 , 18 , 33 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation